The Role of the New Media in the Migratory Experiences of Brazilian Footwear Industry Workers in the South of China - Norberto KUHN JUNIOR; Margarete Fagundes NUNES (El Colegio de la Frontera Norte, A.C., 2012)
Migratory experiences are part of the representative phenomena of contemporary social arrangements since not only goods and capital but also persons move from one part of the earth to another, joining the synergic flows of capitalism organized on a global scale. Empirically, we refer to the migratory experiences of footwear industry workers from Novo Hamburgo, Brazil, who have immigrated to China in recent years. We analyze the strategies adopted by these groups to support their projects to migrate to and settle in China. Above all, we focus on the role played by communications media in the construction of links between the community of origin and the new ethnic environment recreated in foreign lands.